Synthesis, electrochemical and spectroscopic studies of multidodecylated liquid crystalline phthalocyanine-ferrocenylethoxide conjugates for biochemical applications - Davis, Wade Luke (University of the Free State, 2003)
English: This thesis is concerned with the synthesis and characterisation of some ferrocenyl and phthalocyanine derivatives. Symmetrically dodecylated phthalocyanines were obtained by the cyclisation of 3,6-bis(dodecyl)phthalonitrile. Unsymmetrically dodecyl-phthalocyanineferrocenylethoxide conjugates were obtained by the statistical condensation of 3,6-bis(dodecyl)- phthalonitrile and 4-(2'-ferrocenylethoxy)phthalonitrile. The anchoring of the ferrocenyl fragment, which itself is an antineoplastic entity, onto a phthalocyanine was accomplished utilising an ether bond. The electrochemical behaviour of the ferrocenyl and selected phthalocyanine derivatives is reported. Most of the ferrocenyl compounds undergo a one-electron reversible process. Four ring-based electron transfer processes for the metal-free phthalocyanines were observed, whereas the ferrocenyl-phthalocyanine conjugate showed an additional, fifth, redox couple associated with the ferrocenyl moiety. UV/VIS spectroscopy of the non-peripherally dodecyl substituted phthalocyanines showed a red shift in absorption Qmax-band, which holds some advantages for irradiation with low-energy diode lasers during photodynamic cancer therapy. The new phthalocyanines also obeyed the Beer-Lambert law for the concentration range 78-163 )µM (Q-band data) in THF, thus showing no aggregation. The new symmetrical octadodecylated phthalocyanines as well as the hexadodecylphthalocyanine- ferrocenylethoxide conjugates exhibited liquid crystalline mesophase behaviour, which was studied using polarised light optical microscopy and differential scanning calorimetry. The zinc-containing ferrocenyl-phthalocyanine conjugate displayed mesophase behaviour over a larger temperature range (30.9-269.9°C) than the metal-free conjugate (30.4-185.3°C). Variable temperature UVNIS spectra of thin films (ca. 1000 A thick) of the phthalocyanine derivatives cast on glass is also reported for each mesophase.

Afrikaans: Hierdie tesis behels die sintese en karakterisering van sekere ferroseen-en ftalosianienderivate. Simmetries dodesielgesubstitueerde ftalosianine is verkry deur die siklisering van 3,6-didodesielftaloni triel. Onsimmetriese dodesiel- ftalosianien- ferrosenieletoksiedkonj ugate is verkry deur die statistiese kondensasie van 3,6-didodesielftalonitriel en 4-(2'- ferrosenieletoksie) ftalonitriel. Die koppeling van 'n ferrosenielfragment, wat self 'n neoplastiese fragment is, aan 'n ftalosianien is bereik deur van 'n eterbinding gebruik te maak. Die elektrochemiese gedrag van die ferroseniel-en geselekteerde ftalosianienderivate is ook gerapporteer. Meeste van die ferroseenbevattende verbindings ondergaan 'n een-elektron omkeerbare proses. Vier ringgebaseerde elektronoordragprosesse vir die metaalvrye ftalosianien is waargeneem, terwyl die ferroseniel-ftalosianienkonjugate 'n addisionele, vyfde redokskoppel vertoon wat geassosieer word met die ferrosenielfragment. UVNIS spektroskopie van die nie-periferiese dodesielgesubstitueerde ftalosianiene het 'n verskuiwing na rooi in die absorpsie van die Qmaks-bandgetoon. Dit hou sekere voordele in vir die bestraling met lae-energie diode lasers tydens fotodinamiese kankerterapie. Die nuwe ftalosianiene gehoorsaam ook die Beer-Lambert wet vir die konsentrasiegebied 78-163 µM (Q-band data) in THF en vertoon dus geen aggregasie nie. Die nuwe dodesielgesubstitueerde ftalosianiene asook die heksadodesiel-ftalosianienferrosenieletoksiedkonjugate vertoon vloeikristal-mesofase gedrag wat deur middel van gepolariseerde lig optiese mikroskopie en differensiële skanderingskalorimetrie bestudeer is. Die sinkbevattende ferroseniel-ftalosianienkonjugaat vertoon mesofase gedrag oor 'n wyer temperatuurgebied (30.9-269.9°C) as die metaalvrye konjugaat (30.4-185.3°C). Veranderlike temperatuur UV/VIS spektrums van die ftalosianienderivate as dun films (ca. 1000 A dik) op glas is ook gerapporteer vir elke mesofase.
Keywords: Ferrocene; Phthalocyanine; Dodecyl; Electrochemistry; Photodynamic cancer therapy; Aggregation; Mesophase; Thin films; Phthalocyanines -- Synthesis; Dissertation (M.Sc. (Chemistry))--University of the Free State, 2003